2023
DOI: 10.1098/rsos.220786
|View full text |Cite
|
Sign up to set email alerts
|

How keratin cortex thickness affects iridescent feather colours

Abstract: The bright, saturated iridescent colours of feathers are commonly produced by single and multi-layers of nanostructured melanin granules (melanosomes), air and keratin matrices, surrounded by an outer keratin cortex of varying thicknesses. The role of the keratin cortex in colour production remains unclear, despite its potential to act as a thin film or absorbing layer. We use electron microscopy, optical simulations and oxygen plasma-mediated experimental cortex removal to show that differences in keratin cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…For instance, Quinn and Hews (2003) observed a significant increase in skin melaninization under the iris of blue skin, suggesting that melanin plays a crucial role in absorbing wavelengths other than blue. Similarly, Jeon et al (2023) discovered that keratin cortex thickness influences the main reflection peak of feather nanostructured melanosomes, resulting in a structural blue color. Notably, Prum et al (1994) found that non-iridescent green and blue skin colors in birds are produced by coherent scattering of dermal collagen fiber arrays in hexagonal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Quinn and Hews (2003) observed a significant increase in skin melaninization under the iris of blue skin, suggesting that melanin plays a crucial role in absorbing wavelengths other than blue. Similarly, Jeon et al (2023) discovered that keratin cortex thickness influences the main reflection peak of feather nanostructured melanosomes, resulting in a structural blue color. Notably, Prum et al (1994) found that non-iridescent green and blue skin colors in birds are produced by coherent scattering of dermal collagen fiber arrays in hexagonal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This can reveal hidden correlations among variables as starting points for more formal downstream hypothesis testing (e.g., pairwise correlation, chi-squared test). Variables included in our FAMD analysis related to the structural and optical properties of scatterers (summarized in Supplementary Table S1 ) from diverse eukaryotic groups (vertebrates, invertebrates and algae; Prum et al, 1999 ; Prum and Torres, 2004 ; Prum et al, 2004 ; Noh et al, 2010 ; Saenko et al, 2013 ; Teyssier et al, 2015 ; Gur et al, 2015a ; Gur et al, 2015b ; Gur et al, 2020 ; Chandler et al, 2015 ; Hsiung et al, 2015 ; Lopez-Garcia et al, 2018 ; Jeon et al, 2023 ; Surapaneni et al, 2024 ). FAMD analysis and plotting were performed using FactoMineR and Factoextra packages in R software version 4.2.2 ( Lê et al, 2008 ; Kassambara and Mundt, 2020 ; R Development Core Team, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the incoming light travels through the biopolymeric formations largely unhindered; nonetheless, a specific set of wavelengths (those with specific ratios to the size of the structure's periodic patterns) are selectively bounced back and generate angle-dependent iridescent shades found in various insects, birds, and marine creatures. Common examples of structural colors that appears in animals are peacock feathers [54][55][56][57], colorful birds [58][59][60][61], butterfly wings [62][63][64] and beetle exoskeletons [52,[65][66][67][68][69].…”
Section: Photonic Structures In Naturementioning
confidence: 99%